LEAFY, a Pioneer Transcription Factor in Plants: A Mini-Review - Yamaguchi, Nobutoshi (Frontiers in Plant Science, 2021)
A subset of eukaryotic transcription factors (TFs) possess the ability to reprogram one cell type into another. Genes important for cellular reprograming are typically located in closed chromatin, which is covered by nucleosomes. Pioneer factors are a special class of TFs that can initially engage their target sites in closed chromatin prior to the engagement with, opening of, or modification of the sites by other factors. Although many pioneer factors are known in animals, a few have been characterized in plants. The TF LEAFY (LFY) acts as a pioneer factor specifying floral fate in Arabidopsis. In response to endogenous and environmental cues, plants produce appropriate floral inducers (florigens). During the vegetative phase, LFY is repressed by the TERMINAL FLOWER 1 (TFL1)–FD complex, which functions as a floral inhibitor, or anti-florigen. The florigen FLOWERING LOCUS T (FT) competes with TFL1 to prevent the binding of the FD TF to the LFY locus. The resulting FT–FD complex functions as a transient stimulus to activate its targets. Once LFY has been transcribed in the appropriate spatiotemporal manner, LFY binds to nucleosomes in closed chromatin regions. Subsequently, LFY opens the chromatin by displacing H1 linker histones and recruiting the SWI/SNF chromatin remodeling complex. Such local changes permit the binding of other TFs, leading to the expression of the floral meristem identity gene APETALA1. This minireview describes the latest advances in our understanding of the pioneer TF LFY, providing insight into the establishment of gene expression competence through the shaping of the plant epigenetic landscape.